Math, asked by malsawmiralte80, 10 months ago

faxtorise the following in splitting in the middle term 3x^2-x-4​

Answers

Answered by rajkhan99612
3

Answer:

(3x-4)(x+1)

Step-by-step explanation:

3x^2-4x+3x-4

x (3x-4)+1 (3x-4)

(3x-4)(x+1)

I hope this is yousefull for you.

Follow me for more answer.

Answered by memanan03
1

3 {x}^{2}  - x - 4 = 0

3 {x}^{2}  + 3x - 4x - 4 = 0

3x(x + 1) - 4(x + 1) = 0

(x + 1)(3x - 4) = 0

(x + 1) = 0 \:  \:  \: or \:  \:  \: (3x - 4) = 0

x = -1, 4/3

Similar questions